Measuring fundamental jet properties with multiwavelength fast timing of the black hole X-ray binary MAXI J1820+070. Issue 3 (22nd March 2021) - Tetarenko, A J; Casella, P; Miller-Jones, J C A; Sivakoff, G R; Paice, J A; Vincentelli, F M; Maccarone, T J; Gandhi, P; Dhillon, V S; Marsh, T R; Russell, T D; Uttley, P
ABSTRACT: We present multiwavelength fast timing observations of the black hole X-ray binary MAXI J1820+070 (ASASSN-18ey), taken with the Karl G. Jansky Very Large Array (VLA), Atacama Large Millimeter/Sub-Millimeter Array (ALMA), Very Large Telescope (VLT), New Technology Telescope (NTT), Neutron Star Interior Composition Explorer (NICER), and XMM–Newton . Our data set simultaneously samples 10 different electromagnetic bands (radio – X-ray) over a 7-h period during the hard state of the 2018–2019 outburst. The emission we observe is highly variable, displaying multiple rapid flaring episodes. To characterize the variability properties in our data, we implemented a combination of cross-correlation and Fourier analyses. We find that the emission is highly correlated between different bands, measuring time-lags ranging from hundreds of milliseconds between the X-ray/optical bands to minutes between the radio/sub-mm bands. Our Fourier analysis also revealed, for the first time in a black hole X-ray binary, an evolving power spectral shape with electromagnetic frequency. Through modelling these variability properties, we find that MAXI J1820+070 launches a highly relativistic ($Γ =6.81^{+1.06}_{-1.15}$ ) and confined ($φ =0.45^{+0.13}_{-0.11}$ deg) jet, which is carrying a significant amount of power away from the system (equivalent to $\sim 0.6 \, L_{1-100{\rm keV}}$ ). We additionally place constraints on the jet composition and magnetic field strength in the innermost jet base region. Overall, this work demonstrates that time-domain analysis is a powerful diagnostic tool for probing jet physics, where we can accurately measure jet properties with time-domain measurements alone.